Faktor-Faktor yang Mempengaruhi Kejadian Kardiovaskular Mayor pada Wanita Pasca Infark Miokard Akut - Siska Suridanda Danny; Poppy S Roebiono; Amiliana M Soesanto; Manoefris Kasim (The Indonesian Heart Association, 2009)
Background.Cardiovascular mortality had decreased significantly in men during the last 20 years but the decrease of mortality in women stayed more subtle. Age-group analysis toward this lack of decline showed that gender difference especially evident in subjects aged less than 55 years. This study aimed to investigate the rate of Major Adverse Cardiovascular Events (MACE) occurred in women after Acute Myocardial Infarction (AMI) and associated predictors, along with the differences in clinical characteristics between age groups which could potentially cause a disparity in outcome.Methods.This was a retrospective cohort study by medical records analysis. We investigated female patients presenting to Emergency Departement National Cardiovascular Center Harapan Kita Jakarta (NCCHK) with AMI during January-December 2007. Investigation toward the occurrence of MACE was undertaken in February-March 2009. Results.Female patients constituted 22.4% of all patients diagnosed as Acute Coronary Syndrome. There were a total of 168 patients with AMI, followed for 14-26 months (mean follow up time of 16.6 months). The incidence of MACE was 51.7%. Intra hospital mortality was 16.7% while overall mortality was 30.9%. Predictors for MACE were Diabetes Mellitus (DM) with HR 2.293 (95% CI: 1.099-4.783 p=0.027), and coronary lesion affecting 3 vessel/Left Main disease with HR 4.217 (95% CI: 1.907-9.280 p<0.001). Age-group analysis showed that in women more than 55 years of age, predictors of MACE included also DM and coronary lesion affecting 3 vessel/Left Main disease, along with history of previous angina. However, in women less than 55 years of age, the incident of MACE can not be predicted by clinical factors investigated by this study.Conclusions.AMI in women poses a high rate of MACE and death in all age groups. AMI occurred in younger women constitutes a high risk group with different disease profile which is difficult to predict by traditional risk factors.